THE HEURISTIC POTENTIAL OF THE PHENOMENOLOGICAL METHODOLOGY OF DISABILITY RESEARCH - Chernetskyi, Denys (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2025)
The article draws attention to the transgressive effect of the 11 years of war in Ukraine, when a significant public demand from Ukrainians for understanding and researching disability is being formed in a nonlinear and traumatic way. This demand actualizes the subject of the article’s research, which attempts to study the heuristic potential of the phenomenological methodology of disability research in contrast to the medical and social models of disability that are prevalent in modern society (including Ukraine). It is specified that the modernity of a specific phenomenological approach is determined by the possibility of building a trauma-sensitive, non-discriminatory dialogue and a productive conversation about disability here and now. Based on the criticism of phenomenology by modern disability researchers, the article describes the problematic narrow points of classical phenomenological approaches (E. Husserl, M. Heidegger, M. Merleau-Ponty), as well as some early phenomenological models of disability. It is shown that the narrowing of the phenomenology of disability to the phenomenology of disease is methodologically discriminatory towards certain cases of congenital disability. Classical phenomenology, which should focus on describing the experience of corporeality as such, tends to create an artificial dichotomy of the «normative/non-normative» body, thereby moving away from its own basic guidelines. A new and expanded version of the phenomenological model is analyzed, which views disability as a complex, dynamic, and multidimensional phenomenon. Disability here is an interweaving of both intrinsic (medical model) and extrinsic (social model) properties, pre-reflective, attuned (pre-awareness), and reflective aspects that constitute the experience of disability. The conclusion indicates that by overcoming the bottlenecks of classical phenomenological approaches in a new phenomenological model of disability, we must leap to a postphenomenology of disability as a broader view of disability (as mediated by technology). Phenomenology here serves as the methodological basis of postphenomenology, and postphenomenology opens up for the latter the possibility of reconsidering what disability is in the 21st century, in particular in the context of posthumanist challenges.